(untitled) (Research, Society and Development, 2023)
This article seeks to analyze how teachers from the Municipal Network of Fortaleza carry out their reading practices in line with their area of training and how they affect their actions in the classroom. To this end, we use BNC Formation as a point of analysis, considering its three guiding axes: Knowledge, Practice and Engagement. We perceive reading as a framework to expand the teacher’s knowledge around their experience, as well as an element of fundamental importance in the construction of student learning, attributing new conceptions about reality. As specific objectives of this work, we seek to analyze the characteristics of the three axes of BNC Formation that guide the continuing education of teachers; to identify possible gaps in the continuing education of teachers from the Municipal Network of Fortaleza, referring to their reading practices and compare the profiles of teachers from the Municipal Network of Fortaleza in the Basic Education segments. For the methodological development, we carried out a questionnaire on Google Forms, in which we had the participation of teachers from the three segments of Basic Education, (Childhood Education and Elementary School I and II). As results and discussions of the article, we propose to analyze, through the feedback obtained by the questionnaire, how the readings performed by the teachers influence and are influenced by their training.